New Ways of Looking at Democracy. Issue 146 (July 2016) - Hennig, Brett
Abstract : Dr. Brett Hennig is the cofounder and director of the Sortition Foundation (http://www.sortitionfoundation.org/ ). This is an edited extract from his new book, The End of Politicians, to be published by Unbound in late 2016 (https://unbound.co.uk/books/the‐end‐of‐politicians/ ).